The association of workplace smoke-free policies on individual smoking and quitting-related behaviours - Haoxiang Lin; Min Li; Meijun Chen; Yihua Liu; Yuting Lin; Zhao Liu; Zhijie Zheng; Chun Chang (BMC, 2021)
Background Our study aims to provide information about workplace smoke-free (SF) policy coverage in mainland China and to assess the relationship between workplace SF policies and secondhand smoke (SHS) exposure, current smoking, smoking harm awareness and quitting intention among smokers. Method Data from the 2018 Asia Best Workplace Mainland China programme were used to address these aims. This cross-sectional study included 14,195 employees from the 2018 survey and 14,953 employees from the 2019 survey. Logistic regression with year-fixed effects was applied to these data. The dependent variables were SHS exposure, smoking or smoking harm awareness. The explanatory variable was the SF workplace policy. Results A total of 21,275 participants (73.0%) reported working under SF policies. The overall prevalence of smoking and SHS exposure were 20.3% and 52.5%, respectively. The workplace SF policy was significantly associated with lower SHS exposure (OR: 0.48, 95% CI: 0.45-0.51), lower current smoking employees (OR: 0.81, 95% CI: 0.76-0.87) and higher awareness of smoking harm (OR: 1.76, 95% CI: 1.61-1.91). However, workplace SF policy was not significantly associated with quitting intention (OR: 0.99, 95% CI: 0.84-1.16). Conclusion Our study identified that although most companies had established workplace SF policies, the overall prevalence of SHS exposure remained very high. Workplace SF policy is associated with lower SHS exposure, lower overall current smoking and higher awareness of smoking harm. These findings provide valuable evidence to promote such policies in all workplaces.